Infection characteristics of porcine circovirus type 2 in different herds from intensive farms in China, 2022 - Fan, Mingyu; Bian, Lujie; Tian, Xiaogang; Hu, Zhiqiang; Wu, Weisheng; Sun, Leilei; Yuan, Guiqiang; Li, Shuangxi; Yue, Lei; Wang, Ying; Wu, Lili; Wang, Yongquan; et al. (Frontiers in Veterinary Science, 2023)
Introduction Porcine circovirus type 2 (PCV2) is the primary etiological agent of porcine circovirus diseases (PCVD), which are widespread in most pig herds, causing huge economic losses in the global pig industry. Therefore, it is critical to assess the infection characteristics of PCV2 in different swine herds to develop effective strategies against PCVD. Methods In this study, routine diagnostic and monitoring protocols were used to collect 12,714 samples from intensive farms in China, and PCV2 was tested for by qPCR to determine positivity rates and viral loads in samples from different herds and materials. Results PCV2 was found to be prevalent throughout China, and fattening farms had higher positivity rates than breeding farms. The PCV2 positivity rates in breeding farms in Southern China were higher than those in Northern China. Growing–finishing pigs demonstrated the highest positivity rate in the tested samples, while pre-weaning piglets and adult sows had the lowest. Meanwhile, samples with viral loads exceeding 106 copies/mL in growing–finishing pigs had 27.2% positivity, compared to 1.9% and 3.3% in sows and piglets, respectively. The results of the viral loads in the serum samples followed a similar trend. Discussion The findings reveal that PCV2 circulates in different herds from intensive farms, with positivity increasing from pre-weaning to growing–finishing herds. It is urgent to develop effective strategies to reduce PCV2 positivity in growing–finishing herds and prevent viral circulation among pigs.